A systematic NLTE study of very metal-poor stars with metallicity down to −4.3 dex. I. global stellar parameters based on high-resolution spectra - Shi, Jianrong; Zhao, Gang; Liu, Shuai; Zhou, Zeming; Li, Haining; Yan, Hongliang; Alexeeva, Sofya; Zhang, Huawei; Aoki, Wako; Matsuno, Tadafumi; Zhao, Jingkun; Chen, Huiling; et al. (The astrophysical journal, 2025)
Very metal-poor (VMP) stars provide a record of the chemical composition and dynamics of the early Galaxy. Based on the high-resolution and high signal-to-noise ratio spectra from the Subaru Telescope for 103 VMP stars, in this series of papers we homogeneously investigate the nonlocal thermodynamic equilibrium (NLTE) abundances of important astrophysical elements. This sample covers a wide metallicity range from [Fe/H] ∼ −1.7 dex down to −4.3 dex, including 13 objects with [Fe/H] ≤ −3.0 dex. Here, we present a set of homogeneous stellar atmospheric parameters, including the effective temperature, surface gravity, metallicity, and microturbulence velocity with the spectroscopic method, and the NLTE line formation for both Fe i and Fe ii in the classical one-dimensional model atmospheres have been considered. The NLTE effects of the Fe i lines range from ∼0.03 dex to ∼0.3 dex, and increase with decreasing metallicity. In addition, they depend on the surface gravity, which generally increases with decreasing . The largest NLTE effects can be found for the giants of ∼ 2.5 dex. For dwarfs and subgiants, our final effective temperatures are consistent with those derived from the TIRFM scales of A. Alonso et al. with a mean difference of 7.1 ± 100.2 K, while for giants, our results are slightly lower than those from the TIRFM scales of A. Alonso et al. with a mean difference of −69.5 ± 94.1 K. For dwarfs and subgiants, the spectroscopically derived surface gravity is consistent with that estimated based on the Gaia DR3 parallax; however, for giants, the former leads to a 0.2 dex lower surface gravity.
Veröffentlicht: 15. April 2025
Gesehen am 07.10.2025